Barriers and facilitators for healthy lifestyle and recommendations for counseling in endometrial cancer follow-up care: a qualitative study - Anne M. de Korte; Belle H. de Rooij; Dorry Boll; Ingrid van Loon; Noor Vincent; Meeke Hoedjes; Chantal R.M. Lammens; Floor Mols; Marije L. van der Lee; M. Caroline Vos; Nicole P. M. Ezendam (Journal of Psychosomatic Obstetrics and Gynecology)
Objectives Lifestyle promotion during follow-up consultations may improve long-term health and quality of life in endometrial cancer patients. This study aimed to identify barriers and facilitators to improve and sustain a healthy lifestyle that can be translated to behavioral methods and strategies for lifestyle counseling.Methods Endometrial cancer patients from three hospitals were recruited to participate in a semi-structured interview. The data were transcribed and coded. Thematic analysis was applied to identify themes and the behavior change wheel was used as a theoretical framework. Data saturation was confirmed after 18 interviews.Results Barriers included knowledge gaps as well as lack of motivation and environmental opportunities to engage in health-promoting behavior. Facilitators included applying incremental lifestyle changes, social support, positive reinforcements, and the ability to overcome setbacks.Conclusions We propose the following intervention functions: education, persuasion, training, environmental restructuring, and enablement. Suitable behavior change techniques to deliver the intervention functions include information about the consequences of certain behavior, feedback on behavior, credible source, graded tasks, habit formation, restructuring of the environment, prompts/cues, goal setting, action planning, and social support. Including these recommendations in lifestyle counseling could aid lasting lifestyle change since it suits the needs and preferences of patients.